EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF DIGITAL MEDIA IN GRADE V OF UPTD SDN 124398 JL. PERWIRA PEMATANGSIANTAR - Thesalonika, Emelda; Saragih, Ezion; Sianipar, Marupa; Saragi, Yesiska; Oroh, Ory Efata; Manullang, Ivan Viktor; Sitohang, Edward; Munthe, Sri Rizky; Sihombing, Lisbet N (MSJ : Majority Science Journal, 2026)
This classroom action research was conducted as an effort to improve student learning outcomes through the application of digital media in the learning process at the UPT SD Negeri 124388 Jalan Perwira Pematangsiantar. The background of this research is based on the condition of low student learning outcomes influenced by the use of conventional learning methods that are less able to attract students' attention and active participation. The purpose of this research is to determine the effectiveness of the use of digital media in improving student learning outcomes and improving the quality of the learning process in the classroom. This research was conducted in two cycles, each of which includes the planning stage, action implementation, observation, and reflection. The digital media used included learning videos, interactive teaching materials, and technology-based visual media adapted to the learning material. The results of the study showed a gradual increase in student learning outcomes in each cycle, both in terms of material understanding, activeness in learning, and achievement of evaluation scores. In addition, the use of digital media was able to create a more interesting and enjoyable learning atmosphere, thus encouraging students to be more focused and motivated in participating in learning. Based on these findings, it can be concluded that the application of digital media has proven effective in improving student learning outcomes and is worthy of being used as an alternative learning strategy in elementary schools.